First calving date and productivity of Charolais cows in Coahuila, Mexico. - López-Trujillo, Ramiro; García-Elizondo, Roberto; Ruiz-Zarate, Fernando (Agronomía Mesoamericana, 2016)
The aim of the study was to evaluate the effect of first calving date of Charolais cows on their productive efficiency in a cow- calf system in the southeast of Coahuila, Mexico. Ten- year records of the herd were analyzed to test such effect. Each cow (n=201) was assigned to one of the two consecutive calving groups of 42 days each, according to the date of its first calving. Cows calving early lost this trait in subsequent parturitions; calving date repeatability (Ri) was 0.25, indicating that improvement of herd fertility, discarding cows that first calving was late, would be modest. Weaning age and weight of calves showed similar tendencies (p≤0.01). Ri for calf’s weaning weight and cow’s weaning efficiency were 0.11 and 0.27, respectively. Cow’s weaning weight (Ri=0.66) presented a quadratic response to parity number, but late first calving cows consistently weighed less. Cows, that first calving was at the beginning of the calving season, had better productive efficiency as a result of their performance at first calving. . Low calving date Ri indicates that this variable was sensitive to the reproductive and nutritional management of the herd.